James Dennis - Thesis submitted in partial fulfilment of the degree of Doctor of Clinical Psychology (DClinPsych) - Dennis, J (2024)
Systematic Review of Literature This systematic review sought to identify challenges to and facilitators of psychosocial wellbeing, as reported by autistic older adults. EMBASE, MEDLINE and psychINFO databases were searched on 08/05/2024 for quantitative and qualitative research sampling this population that addressed perceived challenges and enabling factors, beyond biological or neurocognitive aspects. 20 papers were included in the review, addressing a range of factors, e.g. mental health condition prevalence, quality of life compared to younger peers, the impact of diagnosis in later life and experiences of menopause. Most papers were rated as demonstrating acceptable quality with overall low risk of bias. Synthesis of findings was completed using a meta-integration approach, culminating in the presentation of mostly complementary qualitative and quantitative findings. The review identified a high prevalence of depression in this group and higher reported quality of life compared to younger peers. Quantitative findings regarding gender differences and qualitative findings about diagnostic experiences could not be integrated due to a lack of evidence from the respective methodological datasets. Limitations were identified, including low ethnic diversity in study samples and relatively low numbers of the oldest autistic older adults. Taken together, and applying ideas from the power threat meaning framework, this review indicates that clinicians must not underestimate the capability of this group in often having found, over time, inventive ways to make features of their autism support their adaptive functioning. Additionally, there remain crucial gaps in service provision and social inequalities which highlight that more needs to be done to close a chasmic psychosocial wellbeing divide compared to non-autistic older adults. Service Improvement Project Positive Behaviour Support (PBS) is the predominant framework used in the UK to promote patients’ quality of life in intellectual disability (ID) services. However, effective implementation is limited by locally-specific operational and cultural factors. This service improvement project (SIP) investigated barriers to, and facilitators of, effective PBS-informed practice through asking frontline nurses and healthcare assistants (HCAs) about their experiences of supporting patients. Data from six semi-structured interviews were analysed using Interpretative Phenomenological Analysis (IPA), resulting in three superordinate themes: Following Your Heart; It’s Really Tough – You Have to be Strong; and Just out of Reach – the Small Things That Make a Big Difference. These themes highlighted how participants experienced close emotional ties to patients, responded to challenges in their roles and wished for more time for targeted patient wellbeing initiatives. These findings have been related to existing literature regarding PBS delivery and used to generate locally-informed service improvement recommendations for implementation by the senior leadership team (SLT). Recommendations include: recognising and providing support for the emotional efforts of staff; increasing confidence in PBS-orientated staff by generating meaningful outcome evidence that dissuades colleagues from using alternative practices; and providing targeted training, making creative use of existing interest and skill in PBS within the team. Theoretically Driven Research Project Hoarding difficulties (HD) affect many people and can cause upset and danger for the person, as well as friends and family, who themselves may experience distress and stigma as a result of clutter. Previous research found that people with HD feel less adequately socially supported compared to individuals with Obsessive Compulsive Disorder (OCD). To evaluate whether people with HD see their support differently, or there is a gap in support quality compared to those with OCD, this study presents the perspectives of 116 people offering support (POS) to people with these conditions (PWC). The research had a two-tailed hypothesis: a) that POS(HD) would not differ on support ratings compared to POS(OCD), or b) that POS(HD) would report comparatively lower ratings across support components. Support quality was measured using an adapted proxy version of the Revised Norbeck Social Support Questionnaire which focusses on the perspective of the supporter. Additional hypotheses predicted that HD would be the more stigmatised condition and that the POS(HD) group would report higher levels of associative stigma (internalised stigma by virtue of having a connection to a stigmatised individual). The design was cross sectional, comparing those supporting OCD with those supporting HD. POS(HD) rated both their wish to support and the perceived success in terms of the PWC’s response as significantly lower, but did not differ in rating the impact support has on themselves. Public stigma was rated more highly by POS(HD) relative to POS(OCD) and associative stigma felt more acutely by POS(HD). Further research involving POS and PWC dyads is needed to investigate what is causing this shortfall in support. Clinical research for HD interventions should also examine how involving POS could enhance treatment outcomes.